The efficacy of 4Cs-based reading to foster 21st-century learning competencies - Imamyartha, David; Fitriyah, Siti Masrifatul; Tasnim, Zakiyah; Puspa, Areta; Fardhani, Aan Erlyana; Wahjuningsih, Eka; Sundari, Siti; Hudori, Rizki Febri; Arya, Bambang (Universitas Pendidikan Indonesia, 2019)
The omnipresence of 4Cs at tertiary education has shifted the attention of language classroom teachings toward the mastery of multifaceted intelligences. Resultant teaching praxis subsequently calls forth students’ high literacy, which affects the nature and extent of success and failure. This study strived to scrutinize how the 4Cs approach in Reading courses scaffolds students’ multidimensional 21st-century learning competencies. Data were collected through online survey and focus group discussion, with deductive and inductive content analysis subsequently operative. The findings have shed lights on how 4Cs-based reading instructions help teachers to create learning environment commensurate with the demand of 21st-century learning, which aids students’ learning in gaining metacognitive tools for high literacy. With clear framework of collaborative work and scaffolding, teachers can trigger and further direct students’ achievement goals and social goals towards high literacy.